In search of the promised land? the Hasmonean dynasty between biblical models and Hellenistic diplomacy - Berthelot, Katell 1972-; Rigaud, Margaret; Vandenhoeck & Ruprecht (Gottingen Vandenhoeck & Ruprecht, 2017)
Title Page -- Copyright -- Table of Contents -- Preface -- Abbreviations -- A Note on the Translations used in this Book -- Introduction. The Historiography of the Hasmonean Period: The Influence of Biblical Models and of Modern Debates on the Creation of a Jewish State -- 1. A brief overview of one hundred years of historical scholarship on the Hasmonean period (ca. 1850â1950) -- 2. The reconquest of the promised land: A ubiquitous paradigm -- 3. Dissident voices -- 4. Reflexions on some of the methodological problems raised by biblical models -- 4.1 The borders of the promised land -- 4.2 The question of the perenniality of the commandment to conquer the promised land -- 4.3 The âconversionâ of non-Jews -- 5. âReligionâ and âpoliticsâ: two problematic categories in the historiography of the Hasmonean period -- 6. The structure of this book and its guiding principles -- Part I. Did the Hasmoneans Seek to Reconquer the Promised Land or Restore Judea? The Account of the Hasmonean Wars in 1 Maccabees -- 1. The First Book of Maccabees: general presentation -- 1.1 The contents of the book -- 1.2 The language, context, date and compositional unity of the book -- 1.3 Parallel accounts: The Second Book of Maccabees and the work of Josephus -- 1.3.1 The Second Book of Maccabees -- 1.3.2 The Judean (or Jewish) War and Jewish Antiquities by Flavius Josephus -- 2. The land: an objective conspicuous by its absence -- 2.1 The conspicuous absence of the issue of the land of Israel from The First Book of Maccabees -- 2.2 The land in 2 Maccabees and in Josephusâ rewriting of 1 Maccabees -- 2.3 The territorial stakes of the Maccabean wars -- 3. The Hasmonean dynastyâs biblical models -- 3.1 A few preliminary reflections on the concept of âBibleâ in the second century B.C.E. -- 3.2 Biblical models and the literary structure of 1 Maccabees
3.3 Joshua, a model for the Hasmoneans? -- 3.4 A sacerdotal family seeking to legitimate its position as a royal dynasty -- 4. The wars against non-Judean peoples: Judeans versus Canaanites? -- 4.1 The prescriptions concerning the Canaanites in the Bible -- Scenario No 1: the expulsion of the Canaanites -- Scenario No 2: herem warfare or the extermination of the Canaanites -- Scenario No 3: slavery or âforced labourâ -- 4.2 The war practices of Judas Maccabeus and his brothers: an attempt to put Deuteronomy 20 into practice? -- 4.2.1 The influence of Deuteronomy on 1 Maccabees -- 4.2.2 The laws of warfare in Deuteronomy 20 and 1 Maccabees -- 4.2.3 The wars waged by Judas, Jonathan and Simon, according to 2 Maccabees and Flavius Josephus -- 4.3 Do we encounter a âCanaaniteâ in a Hasmonean context? (1 Macc 9:37) -- 5. Did the Hasmoneans attempt to purify the land? -- 6. The âinheritance of our fathersâ (1 Macc 15:33â35) -- 6.1 The territorial dispute between the Seleucids and the Hasmoneans, from Judas to Simon -- 6.2 The biblical background of the phrase âthe inheritance of our fathersâ -- 6.3 The parallels between the discourses of the Seleucids and Simon in 1 Maccabees -- 6.4 Understanding Simonâs reply in the context of the territorial conflicts of the Hellenistic era -- 7. The development of a historico-juridical conception of Israelâs right of ownership over the land -- 7.1 The original allotment of the land according to the Book of Jubilees and the Genesis Apocryphon -- The connections between the Book of Jubilees and the Genesis Apocryphon -- The Hellenistic context of the juridical or historico-juridical discourse used to establish the right of ownership -- 7.2 The posterity of this historico-juridical argument in Jewish thought -- Part II. The Era of the Conquests: Rise and Fall of the Hasmonean State
1. The inescapable Flavius Josephus: was his perspective anti-Hasmonean? -- 1.1 Strabo -- 1.2 Nicolaus of Damascus -- 1.3 The Judean (or Idumean) origins of some of Josephusâ criticism of the Hasmoneans -- 1.4 Josephusâ point of view -- 2. The different stages, the nature, and the motivations of the Hasmonean territorial expansion -- 2.1 John Hyrcanus -- The motivations of John Hyrcanus -- 2.2 Aristobulus I -- 2.3 Alexander Jannaeus -- 103â92 B.C.E. -- 92â83 B.C.E. -- 83â76 B.C.E. -- 2.4 Jannaeusâ successors to the throne until 63 B.C.E. -- 3. The âforced conversionsâ -- 3.1 The Idumeans -- 3.1.1 Josephusâ account of the Judaization of the Idumeans -- 3.1.2 Ptolemy the Historianâs account of the Idumeans -- 3.1.3 Straboâs account of the Idumeans -- 3.1.4 Was the Judaization of the Idumeans an innovation on the biblical models? -- 3.2 The Itureans -- 3.3 The questions raised by the case of Pella -- 3.4 Summary -- 3.5 The presentation of the imposition of Judean laws on the conquered territories as a Seleucid idea in 1 Maccabees 10 -- 4. The use of mercenaries -- 4.1 A sign of the Hellenization of the Hasmoneans -- 4.2 The Judaization of non-Judean populations versus the use of foreign mercenaries -- 4.3 The mercenaries and the Judean opposition to the Hasmoneans -- 4.4 The Hasmoneansâ accumulation of riches -- Part III. Polemic, Memory, Forgetting -- 1. The polemic against the Hasmoneans -- 1.1 The critique of the Hasmoneans in the Qumran manuscripts -- 1.1.1 The first two generations: Mattathias and his sons -- 1.1.2 John Hyrcanus -- 4Q379: Was John Hyrcanus the âman of Belialâ? -- 4QTestimonia, a threefold critique of John Hyrcanus -- The Essenes and prophecy -- A list of false prophets (4Q339) -- The fallibility of the prophet Joshua according to 4Q522 -- The rules of war in the Temple Scroll -- 1.1.3 Alexander Jannaeus
The times of wickedness in 4Q390 -- The Pesher on Isaiah (a) (4Q161) -- 4Q448: for or against king Jonathan? -- The Pesher on Nahum -- The Pesher on Habakkuk -- Is there a condemnation of the Hasmonean wars in 4Q471a? -- 1.2 The critique of the Hasmoneans in the Psalms of Solomon -- 2. Memory and Forgetting: the Hasmonean expansion in rabbinic literature -- 2.1 The memory of the Hasmonean victories in rabbinic literature -- 2.1.1 The memory of these victories in Megillat Taâanit -- 2.1.2 Beyond Megillat Taâanit: the memory of the wars of liberation in the rest of rabbinic literature -- 2.1.3 On some of the echoes of Jannaeusâ conquests in the Babylonian Talmud -- 2.1.4 The implications of John Hyrcanusâ gift of prophecy -- 2.2 The critique of the accumulation of powers and the attempt to control the exercise of royal power -- 2.2.1 The critique of the accumulation of powers -- 2.2.2 The attempt to control the kingâs exercise of power -- 2.3 The ambiguity of the Babylonian Talmud -- 2.3.1 The presence of anti-Hasmonean revisions in the Babylonian Talmud -- The chronology of Seder âOlam in b. Avodah Zarah 8bâ9a -- Alexander Jannaeus as the murderer of the Sages -- The account of the fratricidal conflict between Aristobulus II and Hyrcanus II in b. Menahot 64b -- 2.3.2 The Hasmonean dynasty versus the Davidic dynastyin the Babylonian Talmud -- Conclusion -- Excursus: Eupolemusâ perspective on the reigns of David and Solomon -- List of the documents describing the diplomatic relations between the Hasmoneans and Rome before 63 B.C.E. -- Chronology -- Maps -- Bibliography -- Index of ancient sources
Keywords: Bibel; Bibel; Bibel; Frühjudentum; König; Hellenistische Juden